Phosphites in the management of anthracnose on jilo - Alexandre, Elizabeth Rodrigues; Herculano, Luciana Maria; Silva, Josenilda Maria da; Oliveira, Sônia Maria Alves de (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to evaluate the effects of phosphites on anthracnose (Colletotrichum tamarilloi) on jilo at postharvest. Mycelial growth, and production and germination of conidia were evaluated after the application of Ca, K, Mg, Zn, and Cu phosphites at the doses of 0.25, 0.50, 0.75, 1.00, 1.25, 1.50, and 1.75 g L‑1 (in vitro) on the fungus C. tamarilloi. The doses 0.25, 0.75, 1.25, and 1.75 g L‑1 affected fruit in the period postharvest. Chemical attributes and the possible biochemical response were evaluated. The dose of 1.50 g L‑1 was used in the post‑harvest management of anthracnose after fungus inoculation. In vitro, the effective concentration for 50% reduction of mycelial growth and of conidial production and germination (EC50) was achieved for K phosphite lower concentrations. Linear effect was observed for the anthracnose incidence reduction and for the activity increase of oxidative/reactive catalase enzymes, ascorbate peroxidase, and polyphenoloxidase. Potassium phosphite was the most efficient salt against anthracnose, in stored fruit at 13±2°C and 24±2°C, and it has the potential to be used for this disease management.